ZAKAT PROFESI DALAM PERSPEKTIF UU RI NOMOR 23 TAHUN 2011 DAN HUKUM ISLAM - Muhammad Aziz; Sholikah Sholikah (Ulul Albab, 2015)
One of the real object of charity to this day is still debatable zakat profession, although its existence is still debated, but many have been put into practice, including the case that the rule in Indonesia, who wants to know in this article are; how the zakat profession in the legal perspective number 23 year 2011 about the management of zakat and Islamic law?